Smart mobility management in 5G heterogeneous networks. Issue 3 (1st May 2018) - Omheni, Nouri; Bouabidi, Imen; Gharsallah, Amina; Zarai, Faouzi; Obaidat, Mohammad S.
Abstract : Mobility management has always been a challenging and important issue for the next‐generation all‐IP mobile networks. Seamless mobility is one of the requirements to provide real‐time services in such networks. Proxy Mobile IPv6 (PMIPv6) has been developed by the Internet Engineering Task Force (IETF) as a network‐based mobility management protocol to support the mobility of IP devices. Although several designs have been presented in the literature to reduce the amount of PMIPv6 signalling and latency handover, they do not satisfy the real‐time application requirements. In this study, the authors first propose a novel vertical handover algorithm that helps to anticipate the handover process in an efficient manner. The suggested approach is based on PMIPv6 and IEEE 802.21 Media Independent Handover (MIH) standard. The authors also added a new MIH primitive in order to indicate that a handover is needed to be done very soon. The triggering of such process is done thanks to two proposed dynamic thresholds. According to the analytical evaluation and simulation results, the proposed method guarantees a significant reduction of the handover delay and the signalling overhead, handover blocking probability and packet loss.